Comparison of severe hypercholesterolemia patients with and without pathogenic variants. (3rd October 2022) - Nanchen, D; Von Kanel, T; Ehret, G; Brun, N; Sudano, I; Rodondi, N; Rickli, H; Girod, G; Ballhausen, D; Falciano, R; Beer, J H; Gallino, A
Abstract: Introduction: A pathogenic variant causally related to familial hypercholesterolemia (FH) is found in less than half of adults with severe hypercholesterolemia. The characteristics of adults with severe hypercholesterolemia without pathogenic variant have been poorly described, and it remains unclear whether intensive preventive strategies should be recommended. In this study we compared the characteristics of adults with severe hypercholesterolemia with and without pathogenic variant for FH. Methods: Between November 2020 and February 2022, we recruited individuals older than 16 years with a Dutch Lipid Clinic Network (DLCN) score ≥6 and genotyped LDLR, APOB and PCSK9. Participants were part of the multicenter CATCH study, testing the implementation of genetic cascade screening for FH in Switzerland. All genetic analyses were performed in a single central laboratory. Variants classified as likely pathogenic or pathogenic were interpreted as FH-causing. We also assessed socio-economic status, cardiovascular risk factors, lifestyle behavior, and use of lipid-lowering drugs. Results: In total, 150 non-related adults with a DLCN score of ≥6 were included, out of whom 62 (41.3%) had genetically confirmed FH. Most variants were found in the LDLR gene (77%). Overall, 70% were using a lipid-lowering drug and 20% were current smokers. Compared to adults with genetically confirmed FH, those without pathogenic variants were older (57.6 vs 50.4 years old), had lower untreated LDL-cholesterol levels (p<0.001), higher triglyceride levels (p=0.032), higher BMI (p=0.014), and had more frequently hypertension (62.5% vs 36.1%). No socio-economic differences were observed. Although adherence to Mediterranean diet was higher among adults without pathogenic variant, they reached less frequently the recommended level of physical activity than adults with genetically confirmed FH (66.2% vs 82.1%). Xanthomas or xanthelasmas, but not corneal arcus, were more frequent among genetically confirmed FH (5.7% vs 20.3%). Conclusions: Adults with severe hypercholesterolemia and without a pathogenic FH variant had less optimal control of cardiovascular risk factors than genetically confirmed FH. One fifth were smokers and one third of all patients included in this study were not taking any lipid-lowering drugs, regardless of the presence of a pathogenic variant. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swiss Heart Foundation